A new methodology for the measurement of the root canal curvature and its 3D modification after instrumentation. (3rd October 2018) - Christodoulou, Asterios; Mikrogeorgis, Georgios; Vouzara, Triantafillia; Papachristou, Konstantinos; Angelopoulos, Christos; Nikolaidis, Nikolaos; Pitas, Ioannis; Lyroudia, Kleoniki
Abstract: Objective: In this study, the three-dimensional (3D) modification of root canal curvature was measured, after the application of Reciproc instrumentation technique, by using cone beam computed tomography (CBCT) imaging and a special algorithm developed for the 3D measurement of the curvature of the root canal. Materials and methods: Thirty extracted upper molars were selected. Digital radiographs for each tooth were taken. Root curvature was measured by using Schneider method and they were divided into three groups, each one consisting of 10 roots, according to their curvature: Group 1 (0°–20°), Group 2 (21°–40°), Group 3 (41°–60°). CBCT imaging was applied to each tooth before and after its instrumentation, and the data were examined by using a specially developed CBCT image analysis algorithm. Results: The instrumentation with Reciproc led to a decrease of the curvature by 30.23% (on average) in all groups. Conclusions: The proposed methodology proved to be able to measure the curvature of the root canal and its 3D modification after the instrumentation.